E-COURSE BASED ON THE PLATFORM MOODLE IN TEACHING PHYSICS TO FUTURE SPECIALISTS OF RIVER AND SEA TRANSPORT - Cherniavskyі V. (Kherson State University, 2017)
The article considers that the fastest way to include Ukraine into the global educational system is to create conditions for widespread use of the Internet for training purposes, which is considered the most perfect model of communication in the global information society. It is stated that one of the most common and most convenient forms of distance learning for marine institutions of higher education is electronic courses. Their main advantage over traditional forms of education is to provide the conditions for productive individual work of the students. It is shown that the problem of individual work is particularly relevant for marine education, due to the specific schedule of the educational process, including the presence of long-term shipboard training. It is defined the peculiarities of usage of e-learning courses in Physics for training of the specialists of river and sea transport. It is proposed the interpretation of the term "e-learning course in Physics" as an information model of a specific topic or section of "Physics", which displays the oriented basis of cognitive activity of the student, it provides organic and natural formation, regulates mental and emotional processes, predicts the opportunities for educational tasks solving by offered means for stimulating the development of personal cognitive capabilities. The requirements for e-learning courses in Physics are determined and their advantages over other innovative teaching methods towards the realization of methodological features of the educational process are highlighted. The structure of e-learning courses in Physics is proposed and the experience of e-courses using in Physics for bachelors of specialty "River and Sea transport" is described.